Molecular Modelling Simulations And Inhibitory Effects Of Naturally Derived Flavonoids Targeting Platelet-activating Factor Receptor (pafr) - Noraziah Nordin; Juriyati Jalil; Mohd Faiz Abd Ghani; Adib Afandi Abdullah; Rozana Othman (Bentham Science Publication, 2024)
Indexed by WOS/Scopus/ERA